2013
DOI: 10.1128/iai.01036-12
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of Lipoprotein Lipase-Sensitive Molecules Mediates Toll-Like Receptor 2 Activation by Porphyromonas gingivalis

Abstract: Infection by the chronic periodontitis-associated pathogen Porphyromonas gingivalis activates a Toll-like receptor 2 (TLR2) response that triggers inflammation in the host but also promotes bacterial persistence. Our aim was to define ligands on the surfaces of intact P. gingivalis cells that determine its ability to activate TLR2. Molecules previously reported as TLR2 agonists include lipopolysaccharide (LPS), fimbriae, the lipoprotein PG1828, and phosphoceramides. We demonstrate that these molecules do not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 65 publications
(104 reference statements)
3
94
0
Order By: Relevance
“…Other reports, however, describe P. gingivalis LPS preparations as a highly heterogeneous mixture of different types of lipid A species with differential levels of stimulatory potency in their effects on TLR2 and TLR4 (10,14,49). In addition, a few studies demonstrated that TLR2 activity can be attributed to P. gingivalis lipoproteins (50)(51)(52). However, since methods that are more refined than the SDS-PAGE performed in this study (see Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Other reports, however, describe P. gingivalis LPS preparations as a highly heterogeneous mixture of different types of lipid A species with differential levels of stimulatory potency in their effects on TLR2 and TLR4 (10,14,49). In addition, a few studies demonstrated that TLR2 activity can be attributed to P. gingivalis lipoproteins (50)(51)(52). However, since methods that are more refined than the SDS-PAGE performed in this study (see Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Previous investigations into the effect of P. gingivalis LPS on nonpolarized macrophages have shown that the induced immune responses is varied and that many cytokines were only transiently expressed compared to Escherichia coli LPS and other Gram-negative pathogens (7)(8)(9). Furthermore, P. gingivalis LPS is atypical in that it is structurally different from the canonical enterobacterial LPS and has been reported to stimulate both TLR4 and TLR2 (10)(11)(12). The stimulation of TLR4 has been linked to penta-acylated lipid A structures (13)(14)(15); however, the molecular entity for stimulation of TLR2, even in highly purified LPS samples, has not yet been identified (12).…”
mentioning
confidence: 99%
“…Furthermore, P. gingivalis LPS is atypical in that it is structurally different from the canonical enterobacterial LPS and has been reported to stimulate both TLR4 and TLR2 (10)(11)(12). The stimulation of TLR4 has been linked to penta-acylated lipid A structures (13)(14)(15); however, the molecular entity for stimulation of TLR2, even in highly purified LPS samples, has not yet been identified (12). It has been suggested that TLR2 stimulation is due to the presence of novel lipoprotein contaminants that copurify with the P. gingivalis LPS (12).…”
mentioning
confidence: 99%
“…In another study, multiple lipid A species interacted functionally with both TLR2 and TLR4 [15]. However, as already mentioned, the TLR2 agonist activity in P. gingivalis is most likely due to a lipoprotein, and treatment of LPS with lipoproteinase as free LPS substantially attenuated the TLR2 engaging activity [17]. These findings explain previous observations that P. gingivalis LPS can act both as a TLR4 agonist and antagonist, with an end result of varying cytokine secretion profiles [5,11,12].…”
Section: Differences In Lipid a Have Different Effects On Tlr Signallingmentioning
confidence: 99%
“…Although TLR2 activation by P. gingivalis LPS is possible, the difference lies in the form of LPS presented to the host. For example, the protein-free LPS is unable to activate TLR2, whereas the bound LPS on the live bacterium can mediate TLR2 activation via a novel class of lipoprotein lipase-sensitive molecules highlighting the importance of active infection [17]. In essence, and according to Lasica et al [18], the tightly associated or covalently attached protein to LPS on live P. gingivalis accounts for the TLR2 activation.…”
Section: Introductionmentioning
confidence: 99%